Growth Pattern of Paecilomyces lilacinus in Different Eco-friendly Media: Growth Pattern of Paecilomyces lilacinus in Different Eco-friendly Media - Pancholi, Payal (International Journal of Pharmaceutical & Biological Archive, 2020)
Paecilomyces lilacinus is a common saprophytic, filamentous fungus. Morphological characters of P. lilacinus were separate mycelium, hyaline, conidia white to pink colored, and formation of phialides. The growth of P. lilacinus carried out on Sabouraud dextrose agar, coconut, molasses, and potato dextrose agar media at room temperature was better than incubator (25°C). The fungus has the capacity to colonize the rhizosphere and to grow in close association with nematodes. P. lilacinus was mass multiplied in both solid substrate for sorghum grains and liquid media for coconut water. Effect of temperature on the growth of P. lilacinus wasstudied in solid substrate (sorghum grain) and liquid media (coconut water) at different temperature, namely, 15, 20, 25, 30, and 35 ± 1°C. Number of colonies forming units in sorghum grain was found to be maximum at 30 ± 1°C followed by 35 ± 1°C. In liquid media (coconut water) also, maximum dry mycelial weight was recorded at 30 ± 1°C which was on par with 35 and 25 ± 1°C. It shows effect of temperature on the mycelial growth.